Factors that influence job performance among employees in private sector / Mira Izanee Yahya and Muhammad Amirul Syafiq Dzulkifli - Yahya, Izanee; Dzulkifli, Muhammad Amirul Syafiq (Faculty of Business and Management, 2014)
The research study will focus on the topic of job performance in organization, which is important to maintain company performance in order to achieve company goals through its employees itself. The ability of any organization to channel its organizational goals is to retain valuable employees in organization and continued success performance. Therefore, in order to investigate best factor that contribute performance among employees, the focus of this study will be investigated on most factors that influence employees to perform work in an organization.